78.2k views
24 votes
The indefinite integral can be found in more than one way. First use the substitution method to find the indefinite integral. Then find it without using substitution. Check that your answers are equivalent. 6x^5(x^6-2)dx

User Jaykul
by
5.1k points

1 Answer

12 votes

Answer:


6x^5(x^6-2)\,dx =
(1)/(2)(x^6-2)^2+C

Explanation:

To find:


6x^5(x^6-2)\,dx

Solution:

Method of substitution:

Let
x^6-2=t

Differentiate both sides with respect to
t


6x^5\,dx=dt

[use
(x^n)'=nx^(n-1)]

So,


6x^5(x^6-2)\,dx = ∫
t\,dt =
(t^2)/(2)+C_1 where
C_1 is a variable.

(Use ∫
t^n\,dt=(t^(n+1) )/(n+1) )

Put
t=x^6-2


6x^5(x^6-2)\,dx =
(1)/(2)(x^6-2)^2+C_1

Use
(a-b)^2=a^2+b^2-2ab

So,


6x^5(x^6-2)\,dx =
(1)/(2)(x^6-2)^2+C_1=(1)/(2)(x^(12)+4-4x^6)+C_1=(x^(12) )/(2)-2x^6+2+C_1=(x^(12) )/(2)-2x^6+C

where
C=2+C_1

Without using substitution:


6x^5(x^6-2)\,dx = ∫
6x^(11)-12x^5\,dx =
(6x^(12) )/(12)-(12x^6)/(6)+C=(x^(12) )/(2)-2x^6+C

So, same answer is obtained in both the cases.

User MadLax
by
5.8k points